Amyloidosis and spontaneous hepatic bleeding, transcatheter therapy for hepatic parenchymal bleeding with massive intraperitoneal hemorrhage: a case report and review of the literature. (October 2014) - Mousa, Albeir Y; Abu-Halimah, Shadi; Alhalbouni, Saadi; Hass, Stephen M; Yang, Calvin; Gill, Gurpreet; AbuRahma, Ali F; Bates, Mark
Hepatic hemorrhage can be devastating, especially in patients with underlying hepatic pathology. This is a case report of a 50-year-old man who presented to the emergency room with Stage 3 shock as evidenced by a systolic blood pressure of 90 mmHg, a heart rate of 125 beats per minute, respiration of 32, with delayed capillary refill and agitation. At this time, he was found to have a massive spontaneous intra-abdominal hemorrhage with an advanced stage of amyloidosis with multiple organ malfunctions. The initial diagnosis was based on an abdominal computed tomography scan and the patient was taken expeditiously to a hybrid angiography suite for a celiac angiogram. An intraoperative diagnosis of extravasation from amyloid related vasculopathy was made based on the angiographic appearance of hepatic circulation. Coil embolization of the feeding branch of the bleeder was achieved using the interlock coil system and a completion angiogram was done showing complete cessation of active bleeding. The postoperative phase was uneventful and the patient was discharged home on postoperative day three. His postoperative visit at five months later was unremarkable.